PENGUATAN BUDAYA LITERASI ANAK MELALUI OPTIMALISASI TAMAN BACA MASYARAKAT DI KELURAHAN RAKAM, LOMBOK TIMUR - Trie Rizky Yuliani; Galuh Nuranisa Anggiangraeni; Nanda; Raden Razendra Damarjati; Ni Kadek Cahya Puspita Sari; Aji Saputra; Baiq Refa Sapitri; Mila Aulina Agustin; Arvia Norigina; Ni Kadek Ayu Anggi Mitha; M. Bohri Rohman (Universitas Mataram, 2026)
The low level of reading interest and the suboptimal management of the Community Reading Center (Taman Baca Masyarakat/TBM) in Rakam Village served as the background for implementing a literacy program through the Community Service Program (Kuliah Kerja Nyata/KKN). Initial observations revealed inconsistent visitor attendance and an unsystematically organized book collection, highlighting the need to strengthen literacy culture from an early age. This program aimed to optimize the function of the TBM while enhancing the reading interest and enthusiasm of preschool, elementary, and junior high school students through structured and participatory literacy activities. The program was implemented using a descriptive qualitative approach involving observation, interviews, and documentation. The implementation process included problem identification, collaborative planning with the village government and TBM administrators, program implementation, and evaluation. The results demonstrated positive improvements, including the systematic organization of the book collection, the construction of bookshelves, and the enhancement of the reading space into a more comfortable and attractive learning environment, which contributed to increased visitor attendance. Read-aloud sessions, literacy quizzes, and literacy competitions encouraged active participation, enhanced children's self-confidence, and fostered greater enthusiasm for reading. The evaluation indicated a steady increase in TBM visitor attendance from the first to the fourth week, greater participation of children in read-aloud activities, and increased utilization of book collections that had previously been underused due to inadequate organization. Overall, the program successfully revitalized the role of the TBM as a community literacy center and strengthened a sustainable reading culture in Rakam Village.